Reforming the Slovak Public Sector - Demmou, Lilas (OECD Economics Department Working Papers, 2015)
Improving public sector efficiency can help to meet two conflicting objectives: ensuring fiscal consolidation and maintaining room for growth-friendly spending. However, the public sector lags on the application of e-government and e-procurement, insufficiently prioritizes spending, and suffers from budget fragmentation, lack of coordination between ministries and perceived corruption. The regulatory framework could also be more business friendly and the judicial system more efficient. Boosting public sector efficiency requires broad based reforms. Sequencing will be important for the effectiveness of this comprehensive reform effort, and therefore the government should put an initial emphasis on human resource management and the improvement of administrative capacity